Movement behaviours and anxiety symptoms in Chinese college students: A compositional data analysis - Chao, Luomeng; Ma, Rui; Jiang, Weiwei (Frontiers in Psychology, 2022)
Abstract: In the current research, sedentary behaviours, sleep replacements, physical activity and their relationship with several anxiety symptoms among college students. Respondents are recruited from college students, and 1475 of the respondents have been included for analysis. Sedentary behaviours and physical activity have been evaluated using International Physical Activity Questionnaire Short Form, while the duration of sleep has been evaluated based on Chinese-version Pittsburgh Sleep Quality Index. To assess the anxiety symptoms of respondents, the Generalized Anxiety Disorder-7 has been adopted. The compositional data is analysed in R to conduction replacements estimation among physical activity, sedentary behaviour and sleep on anxiety symptoms. According to the results, it will impose a greater influence on the alleviation of anxiety symptoms by substituting sedentary behaviours with physical activity of moderate to vigorous levels. In the current research, the significance of physical activity at moderate to vigorous levels is highlighted in preventing anxiety among college students.